Banking in the British Commonwealth - Sayers, R. S. (Oxford: Clarendon Press, 1952)
The countries whose banking systems are described in this book have two features in common. They are part of the British Commonwealth, and their banking systems have had in a formative stage, close links to London.
Includes bibliographical references.
osc 08/05/2018
Loans
Keywords: Banks and banking